ImPact of 24-hourS non-InvaSIve blood PreSSure monItorIng on hyPertenSIon management In general PractIce - Marija Petek Šter; Janko Kersnik (Zdravniški Vestnik, 2009)
background Ambulatory blood pressure monitoring (ABPM) gives important additional information to office blood-pressure measurements in diagnostic and treatment of patients with high blood pressure. The aim of our survey is to find out the impact of ABPM on management of arterial hypertension in primary care. Patients and We included 339 consecutive patients with uncontrolled arterial hypertension, treated with methods at least two different antihypertensive drug classes in 38 general practitioner’s offices in Slovenia. We randomly divided patients into the test (ABPM) and the control group (office measurements only). After 12 weeks we assessed the impact of ABPM on management of arterial hypertension. results We analysed data of 339 patients: 160 in the testing and 179 in the control group, aged from 34 to 80 years (mean 61.4 years, SD 9.8 years) with mean systolic blood pressure 159.2 (SD 12.5) mm Hg and mean diastolic blood pressure 92.1 (SD 8.7) mm Hg. 45 (28.1 %) of patients after ABPM have controlled blood pressure. Possibility for controlled blood pressure is higher in female (OR = 5.445, 95 % CI: 2.16–13.76) and patients with lower mean office blood pressure (OR = 0.931, 95 % CI: 0.84–0.97). Performance of ABPM did not have impact on the number of hypertension related office visits (1.6 in tested vs. 1.7 in control group, p = 0.306). Patients in the testing group less often underwent changes of antihypertensive drug therapy (52.5 % vs. 66.5 % in the control group, p = 0.009). conclusions White coat effect is common in patients on combined antihypertensive therapy in primary care. APBM did not reduce the number of office visits, but reduced the probability of antihypertensive drug changes.